Gain-switched 311-nm Ti:Sapphire laser might be a potential treatment modality for atopic dermatitis. Issue 7 (September 2016) - Choi, Sun; OH, Chang; Kwon, Tae-Rin; Kwon, Hyun; Choi, Eun; Jang, Yu-Jin; Kim, Hye; Chu, Hong; Mun, Seog; Kim, Myeung; Kim, Beom
Abstract Phototherapy with 311-nm narrowband-UVB (NBUVB) is an effective adjuvant treatment modality for atopic dermatitis (AD). In this study, we evaluated the therapeutic effect of the newly developed gain-switched 311-nm Ti:Sapphire laser device using a NC/Nga mouse AD model. A total number of 50 mice were used in this study. Atopic dermatitis (AD) was induced in mice by exposure toDermatophagoides farina . These, NC/Nga mice were then treated with conventional 311-nm NBUVB or the newly developed gain-switched 311-nm Ti:Sapphire laser. The clinical features, dermatitis severity scores, and scratching behavior were assessed. In addition, serologic analyses including inflammatory cytokines and histological analyses were performed. Gain-switched 311-nm Ti:Sapphire laser improved the AD-like skin lesions, severity, and symptoms of AD in the NC/Nga mouse model. This new laser also modulated the immune response found in the AD model, including hyper-IgE, upregulated Th2 cytokines, and the Th2-mediated allergic inflammatory reaction. Gain-switched 311-nm Ti:Sapphire laser shows therapeutic promise via an immune-modulation mechanism in an AD mouse model. These data suggest that gain-switched 311-nm Ti:Sapphire laser may be useful as a targeted phototherapy modality for AD.